Integration of Topex Satellite Gravity and DEM SRTM Imagery for Subsurface Structure Identification at Tiris Geothermal Area, Lamongan Volcano Complex, Probolinggo, East Java - Siombone, Salman Hamja; Susilo, Adi; Maryanto, Sukir (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2022)
Tiris area is one area that has geothermal prospects. Tiris area is located in the Tiris sub-district, Probolinggo regency, East Java. This study aims to identify the subsurface structure of the Tiris geothermal area using Topex gravity and DEM SRTM imagery data. The Topex gravity data obtained is still in Free Air Anomali (FAA) form, so it is necessary to make Bouguer and terrain corrections to get a complete Bouguer anomaly. A residual Bouguer anomaly is needed to study shallow subsurface structures. This anomaly is obtained by separating the residual and regional anomalies from the complete Bouguer anomaly using the moving average method. The study area has residual Bouguer anomaly values ranging from -0.5 to 2.9 mGal. The low residual Bouguer anomalies are seen in the body of the Lamongan volcano (LV) and the Tiris geothermal area (TGA). The study of subsurface structures is focused on the LV and the TGA through Forward 2D modeling. The A-A' cross-section illustrates the subsurface of LV, while the B-B' cross-section illustrates the subsurface of TGA. Cross-section A-A' modeling results show that the source of the low anomaly is in the second layer D2 = 1.24 g/ at a depth of 4.0 to 0.6 km below sea level and is suspected to be magma because it has a low density. Cross-section B-B' modeling obtained a low anomaly source at the second layer D2 = 2.03 g/ at a depth of 4.0 to 2.8 km below sea level and is suspected to be intrusive rock. The lineament display on the 2D of DEM SRTM map for the 45o and 135o azimuths shows that the TGA region has a high lineament density, and the orientation of the surface geological structure in the study area is dominant in a northwest-southeast direction.